1991
DOI: 10.1002/srin.199101306
|View full text |Cite
|
Sign up to set email alerts
|

Sticking prevention during fine-ore metallization in two-stage smelting-reduction processes

Abstract: Parameters known to have an influence on the sticking tendency of fine iron ores during reduction are discussed in view of their practicability in smelting‐reduction processes. The low sulfur concept, the admixture of inert materials and the coating of the ore particles with carbon are looked at more closely. Sticking tests in a laboratory fluidized bed with a number of iron ores were carried out to investigate the effectiveness of inert additives and of carbon deposition. While the admixture of fine coke and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 12 publications
0
14
2
Order By: Relevance
“…The presence of CO 2 in CO makes the fibrous iron shorter and sparser, especially when the content of CO 2 is 30 vol%, the iron appears as "cactus-like". D. Neuschütz and S. Hayashi et al 34,[54][55][56] suggest that the sulfur content in the reducing gas has an important influence on the morphology of metallic iron and thus on sticking behavior. Usually the gaseous sulfur is considered to have an effect on promoting the formation of fibrous iron.…”
Section: The Bonding Effect Of Iron Whiskersmentioning
confidence: 99%
“…The presence of CO 2 in CO makes the fibrous iron shorter and sparser, especially when the content of CO 2 is 30 vol%, the iron appears as "cactus-like". D. Neuschütz and S. Hayashi et al 34,[54][55][56] suggest that the sulfur content in the reducing gas has an important influence on the morphology of metallic iron and thus on sticking behavior. Usually the gaseous sulfur is considered to have an effect on promoting the formation of fibrous iron.…”
Section: The Bonding Effect Of Iron Whiskersmentioning
confidence: 99%
“…[3][4][5] Approximately 20 years ago, the carbon-adhering process was introduced as an effective method to prevent sticking. [6] An [7] studied the mineral constituents, microstructure, chemical compositions, and reduction degree of the carbon-adhering hematite fines in the fluidization state, and it was found that carbon generated from 2CO = CO 2 + C in 823 K (550°C) adsorption process took place on the mineral reduction process, which could speed up the reduction and prevent the sticking effectively. Hematite was first reduced from Fe 2 O 3 to Fe 3 O 4 , and Fe 3 O 4 was partially converted to FeO subsequently, which indicated that the carbon adhered on the Fe 3 O 4 surface mainly, as also confirmed by the study by Yaojun.…”
Section: Introductionmentioning
confidence: 99%
“…Iron ores with higher surface area and higher porosity used to show higher reducibility. In context with fluidized bed reduction of iron ore, sticking was a main topic for former research . This work is not focussed on sticking, because of process temperatures from ambient temperature up to 760 °C.…”
Section: Introductionmentioning
confidence: 99%
“…In context with fluidized bed reduction of iron ore, sticking was a main topic for former research. [13][14][15] This work is not focussed on sticking, because of process temperatures from ambient temperature up to 760 8C. Such a reduction temperature is too low for significant sticking mechanisms.…”
Section: Introductionmentioning
confidence: 99%